The Effect of Self Efficacy and Task Aversiveness toward Student Academic Procrastination - Melva Syahrial; Netrawati Netrawati; Dina Sukma; Zadrian Ardi (Universitas Negeri Padang, 2022)
This study objective to describe self efficacy , task aversiveness and procrastination of academic, to analyze the influences between self efficacy to procrastination of academic and to analyze the relationship between task aversiveness to procrastination of academic. This research uses descriptive quantitative research methods. The population in this study were student with a sample of 236 people. From result testing hypothesis seen that self efficacy and task aversiveness take effect significant to behavior procrastination academic.